2021
DOI: 10.3390/ijerph18189513
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Suicide Attempts and Suicide Deaths by Jumping from a High Place in Korean Children and Adolescents

Abstract: Jumping from a high place is the most common method of suicide among Korean children and adolescents. The aim of this study was to examine the personal, family, and school life of Korean children and adolescents who chose jumping from a high place, among suicide attempts and suicide deaths, based on teachers’ reports. Data on suicide attempts and suicide deaths by jumping from a high place in children and adolescents were collected through the Ministry of Education in South Korea from 2016 to 2018. We compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This percentage is similar to or slightly higher in other countries than that in Korea [24,28,29,75,95,96]: 22.9% in Singapore [29], 26.6% in rural China [75], 13.1% in New Zealand [24], 20% in Canada [95], 14.3% in Mexico [28], and 30% in Finland [96]. As most adolescents who die by suicide (approximately 80%) use lethal methods during their first suicide attempt, the rate of previous suicide attempts (13.1-30%) is lower than that of adolescents who make repeated suicide attempts (37.9-53.5%) [97][98][99][100][101][102][103]. The rate of death by suicide after a first attempt is higher in adolescents than in adults [28,38,104].…”
Section: Suicide Warning Signmentioning
confidence: 99%
“…This percentage is similar to or slightly higher in other countries than that in Korea [24,28,29,75,95,96]: 22.9% in Singapore [29], 26.6% in rural China [75], 13.1% in New Zealand [24], 20% in Canada [95], 14.3% in Mexico [28], and 30% in Finland [96]. As most adolescents who die by suicide (approximately 80%) use lethal methods during their first suicide attempt, the rate of previous suicide attempts (13.1-30%) is lower than that of adolescents who make repeated suicide attempts (37.9-53.5%) [97][98][99][100][101][102][103]. The rate of death by suicide after a first attempt is higher in adolescents than in adults [28,38,104].…”
Section: Suicide Warning Signmentioning
confidence: 99%
“…One study found that patients hospitalized for an interrupted SA were approximately 3 times more likely to die by suicide compared with patients with an uninterrupted SA (Steer et al, 1988). Another recent study showed that children and adolescents with interrupted and aborted SAs exhibited greater overall difficulties with relationships, conduct problems, and hyperactivity/inattention relative to those with SAs and those who died by suicide (Song et al, 2021). In contrast, other studies have found that compared with those with SAs, adolescent psychiatric inpatients with interrupted and aborted SAs reported less severe depression and suicidal thinking (Hill et al, 2017), and civilian and military psychiatric patients with interrupted and aborted SAs reported less alcohol use (Luk et al, 2020).…”
Section: Empirical Articlementioning
confidence: 99%
“… 8) However, in South Korea, jumping from heights has been the most utilized method of suicide amongst children and adolescents. 9) The reason for this likely lies in the differing national policies towards firearms. Additionally, living in an urban area with high-rise buildings has been correlated with a higher number of intentional fallers, making local infrastructure an important factor to consider when discussing prevention strategies.…”
mentioning
confidence: 99%